PEMBERDAYAAN LITERASI DIGITAL SISWA MELALUI PELATIHAN PENGGUNAAN QUIZIZZZ DI MI ASY-SYIFA - Wiwinda, Wiwinda; Sari, Chintya; Mukhasonah, Putri Mustriana; Rahayu, Septi; Nurhalimah, Ullik; bin Mustamin, Abdul Aziz (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
This study aims to evaluate the effectiveness of using the Quizizzz application as a digital-based learning medium to enhance students' technological literacy at MI Asy-Syifa. The research is motivated by the growing importance of digital literacy in the technology-driven era, particularly in supporting the Merdeka Curriculum, which emphasizes flexibility and the integration of technology in education. A qualitative method was employed, utilizing training sessions that included lectures, demonstrations, and Q&A, involving 39 third-grade students. The findings indicate that Quizizzz enhances student motivation through gamification, though challenges such as limited technological infrastructure and students' low initial understanding were observed. The training successfully introduced Quizizzz features and educated students on the ethical use of technology. The study concludes that Quizizzz has significant potential as an interactive and engaging learning assessment tool, but continuous training and infrastructure support are needed for optimal implementation. This initiative also contributes to the application of the Merdeka Curriculum by leveraging technology to create a more dynamic and effective learning process.